Chinese soft power and its effects on Arab countries: The Arabian Gulf as a model - Hammad Mukhlif, Widad; Abdul-Rawi, Hussein Ali; ABDAL, AAYAD ABDULRIDHA (Al-Adab Journal, 2021)
This research deals with the study of Chinese soft power and its effects on one of the most important regions in the world, which is the Middle East region, and the Arab Gulf region was a model for research, and it was found that through soft power, a country can penetrate other countries through a variety of tools without resorting to hard power. . Three components of soft power were found: Culture, political values ​​and foreign policy, as soft power does not mean concern for national interests only and ignoring the interests of others. By getting to know the components of Chinese soft power that have been identified in research and its continuous growth, China has been able to build its soft power in areas that include (components Political, economic, social and technological). It has played the tools of Chinese soft power: Culture, foreign policy and political values ​​have an important role in establishing the principle of peace and international and regional cooperation, and through China’s pursuit, in its foreign policy, to create a safe environment for economic growth, avoiding conflicts and disputes, and opening up to the world. The study found that there are effects of Chinese soft power in the Arab Gulf region, especially since the Chinese economic rise has made the Arab Gulf states the first supplier of oil, and that China’s investments in the Arab Gulf region in various fields have contributed to the impact of its economic tools in the region, and on the other hand. Chinese exports, including the military industries, increased to the Arab Gulf states, and they occupied advanced ranks in the import table. In addition, China seeks to find an important role for it in the future in protecting international shipping lines in the region to protect its growing economic interests. Politically, it has been shown that China has always emphasized its non-interference in the affairs of the countries of the region and sought to maintain its stability, which had a major role in developing political relations between the Arab Gulf states and China.